Inflammation and autoimmune myasthenia gravis - Huda, Ruksana (Frontiers in Immunology, 2023)
Abstract Myasthenia gravis (MG) is a neuromuscular autoimmune disorder characterized by chronic but intermittent fatigue of the eye- and general body muscles. Muscle weakness is caused primarily by the binding of an autoantibody to the acetylcholine receptors, resulting in blockage of normal neuromuscular signal transmission. Studies revealed substantial contributions of different proinflammatory or inflammatory mediators in the pathogenesis of MG. Despite these findings, compared to therapeutic approaches that target autoantibody and complements, only a few therapeutics against key inflammatory molecules have been designed or tested in MG clinical trials. Recent research focuses largely on identifying unknown molecular pathways and novel targets involved in inflammation associated with MG. A well-designed combination or adjunct treatment utilizing one or more selective and validated promising biomarkers of inflammation as a component of targeted therapy may yield better treatment outcomes. This review briefly discusses some preclinical and clinical findings of inflammation associated with MG and current therapy approaches and suggest the potential of targeting important inflammatory marker(s) along with current monoclonal antibody or antibody fragment based targeted therapies directed to a variety of cell surface receptors.